The Blows and Capoeira Movements From the Caricatures of Calixto Cordeiro - Araújo, Paulo Coêlho; Jaqueira, Ana Rosa (Frontiers in Psychology, 2020)
This study analyses some elements of the historical and social nature of Capoeira, such as the juridical-political, the clothing, the symbolic and the identity, but, essentially, those of a physical and linguistic nature, from the caricatures produced by Calixto Cordeiro, which illustrated the work of Lima Campos in 1906. In this work, a multi-method process was applied, represented by the presuppositions of Historical Archeology, the interpretation of images indicated by Panofsky, and the documental analysis of various sources. The use of these presuppositions and the confrontation of sources of diverse natures allowed us to interpret the signs, symbols, and meanings from the facts and data described by Cordeiro, about Capoeira presented by different literates. The results of these analyses showed substantial information about the blows/moves of this struggle, as well as its different names, slang and expressive forms, often associated with different groups of practitioners from different Brazilian cities.